The effects of heat stress on morphological properties and intracellular signaling of denervated and intact soleus muscles in rats. Issue 15 (7th August 2017) - Ohira, Takashi; Higashibata, Akira; Seki, Masaya; Kurata, Yoichi; Kimura, Yayoi; Hirano, Hisashi; Kusakari, Yoichiro; Minamisawa, Susumu; Kudo, Takashi; Takahashi, Satoru; Ohira, Yoshinobu; Furukawa, Satoshi
Abstract: The effects of heat stress on the morphological properties and intracellular signaling of innervated and denervated soleus muscles were investigated. Heat stress was applied to rats by immersing their hindlimbs in a warm water bath (42°C, 30 min/day, every other day following unilateral denervation) under anesthesia. During 14 days of experimental period, heat stress for a total of seven times promoted growth‐related hypertrophy in sham‐operated muscles and attenuated atrophy in denervated muscles. In denervated muscles, the transcription of ubiquitin ligase, atrogin‐1/muscle atrophy F‐box ( Atrogin‐1 ), and muscle RING‐finger protein‐1 ( MuRF‐1 ), genes was upregulated and ubiquitination of proteins was also increased. Intermittent heat stress inhibited the upregulation of Atrogin‐1, but not MuRF‐1 transcription. And the denervation‐caused reduction in phosphorylated protein kinase B (Akt), 70‐kDa heat‐shock protein (HSP70), and peroxisome proliferator‐activated receptor γ coactivator‐1 α (PGC‐1 α ), which are negative regulators of Atrogin‐1 and MuRF‐1 transcription, was mitigated. In sham‐operated muscles, repeated application of heat stress did not affect Atrogin‐1 and MuRF‐1 transcription, but increased the level of phosphorylated Akt and HSP70, but not PGC‐1 α . Furthermore, the phosphorylation of Akt and ribosomal protein S6, which is known to stimulate protein synthesis, was increased immediately after a single heat stress particularly in the sham‐operated muscles. The effect of a heat stress was suppressed in denervated muscles. These results indicated that the beneficial effects of heat stress on the morphological properties of muscles were brought regardless of innervation. However, the responses of intracellular signaling to heat stress were distinct between the innervated and denervated muscles. Abstract : Repeated heat stress application to rats using a warm water bath (42°C, 30 min/day, every other day) promoted growth‐related hypertrophy in sham‐operated soleus muscles and attenuated atrophy in denervated soleus muscles. The results indicated that the beneficial effects of heat stress on the morphological properties of muscles were induced regardless of innervation. However, the responses of intracellular signalings to the heat stress were distinct between the innervated and denervated muscles.